A STUDY OF MEDICATION ERRORS IN GENERAL MEDICINE WARDS OF THE SOUTH INDIAN TERTIARY CARE HOSPITAL - Sinha, Garima; Acharya, Leelavathi D; Tunga, Girish; Mathews, Treasa (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To identify and evaluate medication errors, opportunities like medication documentation errors and possible drug-drug interactions by a clinical pharmacist, in general, medicine wards of the South-Indian tertiary care hospital. Methods: A study was conducted for a period of 6-month. The data were collected by chart review method from the inpatient records from the day of admission to the day of discharge. If medication error or any opportunity to cause error was observed, it was documented and clinical pharmacist interventions were done. The parameters, such as medication error rate, types of errors, opportunities of errors, and outcome of errors, were evaluated. Results: A total of 32 medication errors were reported in 497 patients and the medication error rate was 6.4%. Administration errors (28; 87.5%) were found to be higher than prescription errors (4; 12.5%). Omission error was the most common (12; 42.9%) administration error. Factors which increase the risk of medication errors such as medication documentation errors were found in 316 (63.6%) medication orders and 203 (40.8%) had 574 possible drug-drug interactions of which the majority (65.2%) of the interactions were of moderate severity. The outcome of error was found to be error, no harm category for the majority (90.6%) of errors. 32 pharmacist interventions were done and 29 (90.6%) were accepted by health-care professionals. Conclusion: A medication error reporting is a new and evolving concept in Indian hospitals. This study highlights the role of a clinical pharmacist in detection, evaluation, and prevention of medication errors in an Indian hospital. Keywords: Medication error, Hospital, Medication error outcome, Clinical pharmacists’ intervention, Documentation errors.